Virus-Induced T Cell-Mediated Heterologous Immunity and Vaccine Development - Balz, Kathrin; Trassl, Lilith; Härtel, Valerie; Nelson, Philipp P.; Skevaki, Chrysanthi (Frontiers in Immunology, 2020)
Heterologous immunity (H.I.) is a consequence of an encounter with a specific antigen, which can alter the subsequent immune response to a different antigen. This can happen on the level ofat the innate immune system level – often called trained immunity or innate immune memory – and/or on the level ofat the adaptive immune system level involving T memory cells and antibodies. Viruses may also induce T cell-mediated H.I., which can confer protection or drive immunopathology against other virus subtypes, related or unrelated viruses, other pathogens, auto- or allo-antigens. It is im-portant to Uunderstanding of the underlying mechanisms is important for the development of antivi-ral “universal” vaccines and broader T cell responses rather than only just subtype-specific antibody responses such as in the case of influenza. Furthermore, knowledge on about determinants of vaccine-mediated H.I. may inform public health policies and provide suggestions for repurposing of existing vaccines. Here, we introduce H.I. and provide an overview of evidence on virus- and antiviral vaccine-induced T cell-mediated cross-reactive responses. Furthermore, wWe also discuss the factors influencing final clinical outcome of virus-mediated H.I. as well as non-specific beneficial effects of live attenuated antiviral vaccines such as measles and vaccinia. Available epidemiological and mechanistic data have implications both for the development of new vaccines developments but alsoand for personalized vaccinology, which are being presented. Finally, we formulate future research priorities and opportu-nities are formulated.